Knowledge, attitudes and practises toward premarital genetic testing for rare genetic disorders among Omani families at Sultan Qaboos University Hospital - Al, Fori Amel (Department of Pathology, 2025)
In the Sultanate of Oman, the pronounced prevalence of consanguineous unions is associated with an elevated occurrence of rare autosomal recessive disorders. Presently, at the national level, the existing premarital screening (PMS) initiative primarily targets hemoglobinopathies, which are particularly prevalent within the country and not necessarily associated with consanguineous marriages. Conversely, there is an absence of a comprehensive national premarital screening programme to identify individuals at risk of rare genetic disorders. Premarital genetic testing (PMT) is currently provided at the two national genetic centres exclusively for family members deemed to be at risk, a strategy implemented as part of a familial-centred approach following the diagnosis. One of these two centres is the Genetics and Developmental Medicine Clinic (GDMC) at Sultan Qaboos University Hospital (SQUH) which provides this service following every newly diagnosed family for at-risk family members. Aim: To explore the knowledge, attitudes, and practices toward premarital genetic testing targeting familial mutation for rare genetic disorders. Methods: This cross-sectional quantitative study utilised a snowball sampling approach targeting the Omani families who were followed up by the GDMC at SQUH between 2012 and 2020 and had a confirmed diagnosis. The data were collected via an online Google questionnaire from 1118 participants who were officially registered in the records of the GDMC. The participants were invited to participate and were grouped into four categories based on their marital status, the number of offspring, and their children's health status: Group 1 (G1) were single or engaged individuals; Group 2 (G2) consisted of individuals who were married, divorced, or widowed without any children; Group 3 (G3) included individuals who were married, divorced, or widowed with healthy offspring; and finally, Group 4 (G4) were individuals who were married, divorced, or widowed and had at least one child affected by a genetic condition. In total, 659 responses were received, and the data were statistically analysed to describe the knowledge of the participants about premarital testing, their attitudes and practices towards the testing, and the implications of their carrier status results. Results: A total of 659 responses were received, with 342 participants receiving the questionnaire directly from the main researcher and 317 via snowball sampling. Participants were categorized into four groups based on their marital status, number of offspring, and their children's health status. Group 1 (G1), comprising 19% (n=126), consisted of single or engaged individuals. Group 2 (G2), accounting for 8% (n=52), included individuals who were married, divorced, or widowed without children. Group 3 (G3), representing 35% (n=230), included individuals who were married, divorced, or widowed with healthy offspring. Lastly, Group 4 (G4), making up 38% (n=251), comprised individuals who were married, divorced, or widowed and had at least one child affected by a genetic condition. The majority of the studied group (55%; n=362) had completed their undergraduate studies. Among the participants, 79% (n=523) had attended the clinic, while 21% (n=136) had not visited the clinic previously. Ninety per cent of the parents in G4 were unaware of a pre-existing history of a genetic condition within their families before the birth of their affected child. Furthermore, 75% of these parents lacked awareness of the PMT services. Seventy-nine per cent of individuals in G4 shared their genetic diagnosis with family members, and 78% recommended that their relatives consider undergoing PMT. Regarding the various relative groups, 91% of individuals in G1 (single/engaged), 87% of those in G2 (married/divorced/widowed without children), and 79% of G3 (married/divorced/widowed with healthy children) were aware of a genetic diagnosis in their families. Furthermore, 88% of individuals in G1, 80% of G2, and 62% of G3 were informed about the availability of PMT services. There was a consensus across the groups regarding the psychological and psychosocial burden of the genetic condition on the families and the effectiveness of PMT as a preventative option against the recurrence risk of the genetic condition in future generations. The uptake rate of PMT across G1, 2 and 3 was 60% (n=266) with 45% (n=120) identified as carriers for the causative variant and 55% (n=146) were non-carriers. The primary motivations behind opting for genetic testing included a desire to ascertain carrier status, prevent the transmission of the genetic disorder to subsequent generations, and circumvent the inherent complexities and hardships associated with having a child with a rare genetic condition. Conversely, the prevailing reasons for refraining from pursuing PMT included a lack of awareness regarding the genetic diagnosis in the family and the availability of PMT, not having an interest in acquiring knowledge of their carrier status, fear that the test outcome might affect their preferred marital choices and a belief that PMT interferes with God's will. Both carriers and non-carriers expressed strong approval of the ease with which they can share their carrier status results with their families and spouses. Likewise, both carriers and non-carriers highly endorse the simplicity of encouraging their spouses to undergo PMT. Furthermore, both carriers and noncarriers highly approved the impact of their carrier status results on their marriage opportunities. Among carriers in G1, 2, and 3, there was variability in their opinion of how their carrier status results might affect their marriage plans, particularly in terms of potential cancellations due to incompatible genetic outcomes. There was a consensus among the relative groups regarding the impact of the family history of the genetic diagnosis on their marriage opportunities. Moreover, most respondents considered the appropriate timing for PMT before initiating the marriage plan and at the age of 18 years old. Furthermore, 60% (n=400) of participants recommended that at-risk couples who received incompatible genetic results through PMT attend a genetic counselling session before proceeding with their marriage plans, while 27% of participants advised them to cancel their marriage plans. Concerning the mandatory implementation of PMT services, 58% (n=386) of participants supported this suggestion, 27% (n=181) expressed opposition, and 14% (n=29) remained neutral. Conclusion: It is evident that parents of affected children play a crucial role in disseminating information about genetic diagnoses to their relatives and encouraging them to undergo PMT. This is underscored by their high awareness of the genetic condition's existence, its psychological and psychosocial impacts on families, and the widespread acceptance of PMT among related groups. Our participants strongly believe in the efficacy of PMT as a preventive measure against the recurrence of genetic conditions and advocate for its mandatory implementation. This support stems from their personal interest in knowing their carrier status and their desire to prevent disease transmission. The high collective awareness within these families also facilitates the disclosure of carrier status results to family members and spouses, as well as encouraging spouses to undergo PMT. Participants also acknowledge the impact of carrier status results on marriage opportunities, including potential cancellations due to incompatible genetic findings